Integrating Knowledge Activities for Team Innovation: Effects of Transformational Leadership. (May 2018) - Jiang, Yuan; Chen, Chao C.
We conducted two studies to explore integrative, knowledge-centered team mechanisms through which transformational leadership affects team innovative performance. In the first study, using temporarily assembled project teams working on knowledge-intensive tasks, we found that transformational leadership promoted within-team knowledge sharing and team innovative performance through an integration mechanism manifest as team cooperative norms, and such a mediation process was significant even after controlling for another mediation process of team autonomy. In the second study, using permanent work teams in various functional areas, we replicated the integrative mechanism and associated transformational leadership with external team knowledge acquisition, which further moderated the relationship between knowledge sharing and innovation. Our findings point to the importance of the integration function of transformational leadership in enhancing collective innovation.